Long-standing necrobiotic xanthogranuloma limited to the skin: A case report - Anne-Sophie Smilga (SAGE Publishing, 2021)
Necrobiotic xanthogranuloma is a rare non-Langerhans cell histiocytosis with a known association with monoclonal gammopathies and malignant conditions. There is a lack of consensus regarding the management of necrobiotic xanthogranuloma. In this case report, the patient is diagnosed with a long-standing necrobiotic xanthogranuloma limited to the skin. Although all initial investigations were reassuring, the patient remains at a higher risk of developing a malignant condition. The goal of the authors is to highlight the need for clearer investigation and follow-up guidelines.